Pelatihan Lesson Study Dalam Peningkatan Kompetensi Pedagogik Bagi Guru SMK - Bastian, Adolf; Firdaus, M.; Rizky, Ramanda (Faculty of Engineering University of Pahlawan Tuanku Tambusai, 2023)
Community service activities are a form of the Tridharma of Higher Education carried out by the service team at partner institutions, namely Pro Skill Indonesia Health Vocational School located in Perawang. This service aims to improve the pedagogical competence of teachers through Lesson Study activity training. The method used is in the form of material delivery by resource persons and discussions. The training was attended by 12 teachers from various departments in the school. This training consists of a cycle that has three stages, namely planning (plan), implementation (do) and reflection (see). Before delivering the material, the resource person prepares learning tools and media needed in Lesson Study training. Then, the model teacher conducts teaching and learning activities supervised by an observer. After that, the results of the observation are observed and from the findings it can be concluded that the Lesson Study activity training is able to improve teachers' pedagogical competence seen from the professional aspects and teacher discipline in carrying out teaching and learning activities in the classroom.